Family dynamics in transthyretin‐related familial amyloid polyneuropathy Val30Met: Does genetic risk affect family functioning?. Issue 5 (14th August 2018) - Lopes, Alice; Rodrigues, Carla; Fonseca, Isabel; Sousa, Alexandra; Branco, Margarida; Coelho, Teresa; Sequeiros, Jorge; Freitas, Paula
Abstract : Adult‐onset, chronic, genetic diseases like transthyretin‐related familial amyloid polyneuropathy Val30Met (TTR‐FAP Val30Met), have a major psychosocial impact not only on patients, but also on families. Genetic risk may therefore be an increased factor in psychosocial impact of the disease on these families' functioning. To evaluate impact of genetic risk, a study was conducted to perceive the impact of the illness on families' functioning. Groups of TTR‐FAP Val30Met patients, pre‐symptomatic carriers, partners and patients with multiple sclerosis (MS), a non‐hereditary disease, were studied. Sample included 190 adults: 87 patients and 28 pre‐symptomatic carriers for TTR‐FAP Val30Met, 41 partners and 34 patients with MS. Family Adaptability and Cohesion Scale IV (FACES IV) and a social‐demographic questionnaire were applied. No significant differences were observed between patients and pre‐symptomatic carriers and both these and their partners regarding cohesion and flexibility. MS patients scored significantly higher in median scores for balanced scales. Satisfaction and communication levels were also lower in patients with TTR‐FAP Val30Met than with MS. Family functioning was perceived as balanced by most TTR‐FAP Val30Met patients and pre‐symptomatic carriers. These families may be considered as mostly healthy. Difficulties in family communication should be taken into account when caring for these families. Abstract :